(untitled) (Global Journal of Human-Social Science, 2024)
person s well-being and success depend largely on the experiences they were exposed to in childhood A young child who has access to key early childhood development services nutrition health social protection and early learning and who benefits from nurturing parental care has a better chance of developing optimally Much more than before decisionmakers around the world understand the devastating socio-economic consequences of poor early childhood development This is why they are now further increasing their investments in early childhood development programs Cote d Ivoire over the last decade has tried as best it can to invest in early childhood development This article presents an analysis of early childhood education in Ivorian society With this in mind this study answered four questions 1 What is the situation of early childhood education in C te d Ivoire What is the importance of early childhood education in the economic context of Cote d Ivoire What are the challenges of early childhood education in C te d Ivoire What attitudes should be taken to meet the challenges of this type of education A qualitative research approach involving an analysis of documents and publications was applied in carrying out this research